Perceived life threat in children during the COVID-19 pandemic: associations with posttraumatic stress, anxiety, and depressive symptoms - BreAnne A. Danzi; Jessica T. Kelly; Ellen A. Knowles; Evan T. Burdette; Annette M. La Greca (BMC, 2024)
Abstract Defining children's "trauma exposure" in the context of the COVID-19 pandemic has been a source of debate. Children were exposed to threatening messaging about COVID-19 but might interpret this information differently than adults. Perceived life threat (PLT), the belief that one's life is in danger, has been identified as a robust predictor of posttraumatic stress symptoms (PTSS), and may be a better predictor of PTSS than actual life threat (ALT). This study investigated parent reports of children's self-PLT (belief that they might die from COVID-19) and family-PLT (belief that a family member might die from COVID-19). The aims were to compare PLT to ALT, evaluate their associations with children's psychological functioning, and identify risk factors associated with PLT. We hypothesized an association between PLT and children's psychological functioning in the context of the COVID-19 pandemic. Parents (N = 140) reported on their child's (M age = 9.81 years, 47% female) pandemic experiences, psychological functioning, and both self-PLT and family-PLT. Results revealed self-PLT for 10% of the children and family-PLT for 43% of the children, yet only 6% experienced ALT (i.e., they or their parent tested positive for COVID-19). Children with reported self- or family-PLT had higher PTSS, depressive symptoms, anxiety symptoms, and functional impairment compared to children without these reported beliefs. PLT, but not ALT, was associated with psychological outcomes. Children with only PLT had greater PTSS and impairment than children with ALT. There were differences in parental functioning and pandemic-related information/media exposure between children with and without PLT. Children's perceptions, rather than objective experiences, may be more central to their psychological functioning. This has implications for screening for pandemic-related symptomatology in children as traditional trauma exposure measures may not adequately identify distressed children.